Less Invasive Rotational Acetabular Osteotomy for Hip Dysplasia - Maruyama, Masaaki (Springer-Verlag, 2012)
BACKGROUND: Broad dissection with a long skin incision and detachment of the gluteus medius muscle performed for rotational acetabular osteotomy (RAO) can result in weakness in abduction strength of the hip. We use a surgical procedure for RAO that minimizes operative invasion of soft tissue and reduces incision length compared with conventional procedures. QUESTIONS/PURPOSES: We evaluated the clinical results of this less-invasive RAO comparing it with the more-invasive prior procedure with respect to improvement in clinical hip scores and radiographic coverage and overall hip survival after the procedure. METHODS: In this less-invasive exposure, the medial gluteus muscle is retracted to expose the ilium without detachment from the iliac crest. Similarly, the rectus femoris muscle tendon is retracted, not excised. The lateral part of the osteotomized ilium is cut to form the bone graft instead of harvesting it from the outer cortical bone of the ilium. Between 2000 and 2009, 62 patients (71 hips) underwent this procedure. Twenty-eight hips had early-stage osteoarthritis and 43 had advanced-stage osteoarthritis. Mean patient age was 40 years at the time of surgery. We evaluated improvement in hip scores (Merle d’Aubigné-Postel, Japanese Orthopaedic Association) and radiographic appearance (lateral center-edge angle, Sharp’s angle, acetabular head index [AHI]). Kaplan-Meier survivorship analysis was performed. Mean followup was 5 years (range, 2.0–10.4 years). RESULTS: Clinical hip scores improved postoperatively. On average, lateral center-edge angle, Sharp’s angle, and AHI improved by 38°, 11°, and 42%, respectively. Predicted 10-year survival rates were 100% and 72% for hips with early- and advanced-stage osteoarthritis, respectively. CONCLUSIONS: In hips with early-stage osteoarthritis treated by this less-invasive approach, no progression of osteoarthritis was documented and Trendelenburg gait was avoided. However, further investigation is necessary for hips with advanced-stage osteoarthritis. LEVEL OF EVIDENCE: Level IV, therapeutic study. See Guidelines for Authors for a complete description of levels of evidence.